TRPV2 channel inhibitors attenuate fibroblast differentiation and contraction mediated by keratinocyte-derived TGF-β1 in an in vitro wound healing model of rats. Issue 3 (June 2018) - Ishii, Taro; Uchida, Kunitoshi; Hata, Shozaburo; Hatta, Mitsutoki; Kita, Tomo; Miyake, Yuki; Okamura, Kazuhiko; Tamaoki, Sachio; Ishikawa, Hiroyuki; Yamazaki, Jun
Highlights: Role of TRP channels in wound contracture is elucidated using a reconstruction model. Keratinocyte-derived TGF-β1 secretion and fibroblast differentiation are clarified. TRPV2 inhibitors attenuate TGF-β-mediated contraction of the model. TRPV2 channels are markedly expressed in this model. TRPV2 is a possible promising target to ameliorate scar formation. Abstract: Background: Keratinocytes release several factors that are involved in wound contracture and scar formation. We previously reported that a three-dimensional reconstruction model derived from rat skin represents a good wound healing model. Objective: We characterized the role of transient receptor potential (TRP) channels in the release of transforming growth factor (TGF)-β1 from keratinocytes and the differentiation of fibroblasts to identify possible promising pharmacological approaches to prevent scar formation and contractures. Methods: The three-dimensional culture model was made from rat keratinocytes seeded on a collagen gel in which dermal fibroblasts had been embedded. Results: Among the TRP channel inhibitors tested, the TRPV2 inhibitors SKF96365 and tranilast attenuated most potently keratinocyte-dependent and — independent collagen gel contraction due to TGF-β signaling as well as TGF-β1 release from keratinocytes and α-smooth muscle actin production in myofibroblasts. Besides the low amounts detected in normal dermis, TRPV2 mRNA and protein levels were increased after fibroblasts were embedded in the gel. TRPV2 was also expressed in the epidermis and keratinocyte layers of the model. Both inhibitors and TRPV2 siRNA attenuated the intracellular increase of Ca 2+ induced by the TRPV agonist 2-aminoethoxydiphenyl borate in TGF-β1-pretreated fibroblasts. Conclusion: This is the first study to show that compounds targeting TRPV2 channels ameliorate wound contraction through the inhibition of TGF-β1 release and the differentiation of dermal fibroblasts in a culture model.